The Occasionalist Society In Robert Musil’s Novel: « The Man Without Qualities » - Anter, Andreas (Eurostudia)

(untitled) (Le Centre canadien d’études allemandes et européennes, 2014)
Robert Musil’s Novel “The Man Without Qualities” has been classified in many ways: as historical novel, as experimental novel, as psychological novel, as social novel. The essay discusses these descriptions critically by combining three perspectives. First, by considering the remarks Musil made himself on his novel in his diaries, in his essays, and in the novel’s draft chapters. Second, by tracing back the answers provided by literary theory in recent decades. Third, by drawing on Carl Schmitt’s concept of occasionalism which he originally coined in examining the literary discourse of political romanticism. The essay comes to conclude that “The Man Without Qualities” can be characterized precisely by its occasionalist structure. The endless conversation in the occasionalist society of Kakania furthermore correlates with the structure of an endless – and therefore unfinished – novel.